Characteristics of Struvite Precipitate from Palm Oil Mill Effluent - Mohd Yuhyi, Mohd Tadza; Hazwani Hawa, Mohammad Sobani; Nur Ain Farhana, Ghani (Akademi Sains Malaysia & Confederation of Scientific & Technological Association in Malaysia (COSTAM), 2015)
Palm oil mill effluent (POME), a residual liquid waste obtained after extraction of oil from the fruits of oil palm is considered one of the main source of contamination of water course in Malaysia. POME contained significant amount of nutrients, organic matter and total suspended solids. Recovery of nutrients from POME would be beneficial for agricultural purposes. In this study, to recover nutrient from POME, a lab-scale study was performed to investigate the efficiency of struvite precipitation method. Struvite precipitation was conducted on raw POME using MgCl2.6H2O + Na2HPO4.12H2O at pH 8. At the end of the test, the water content, mineral and chemical compositions of the precipitate obtained were investigated. In addition, the fertility of the precipitate was evaluated by a set of pot trial tests using Scindapsus Aureus. Test results indicated that, after precipitation test, 92.2% ammonium nitrogen and 100% phosphorus were recovered. X-ray diffraction (XRD) and X-ray fluorescent (XRF) analyses indicated that, after purification, the precipitate is similar to that of struvite. The purified precipitate extracted in this study was found to have a water content of 2799%. Based on the fertility tests, it was found out that the growth of Scindapsus Aureus using struvite precipitate obtained from this study was greater compared to the growth using commercially available fertilizer.